(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Energy harvesting is the conversion of available mechanical vibration energy into electrical energy that can be employed for different purposes. Several works have investigated the development of linear vibration energy harvesters that are efficient in a very narrow bandwidth around the fundamental resonance frequency. Nowadays, many researches have included different kinds of nonlinearities to expand the bandwidth of the energy harvesters. This paper deals with the use of smart materials for energy harvesting purposes. Basically, piezoelectric and shape memory elements are combined to build an energy harvesting system. The analysis is developed considering a one-degree of freedom mechanical system where the equation of motion is formulated by assuming the electromechanical coupling provided by a piezoelectric element and the restitution force provided by shape memory element described using a polynomial constitutive model. Numerical results indicate that the inclusion of the SMA element can dramatically change system dynamics, showing different kinds of responses including periodic and chaotic regimes.